Pengaruh Stres Kerja dan Kepuasan Kerja terhadap Turnover Intention Karyawan PT. Daya Anugrah Mandiri Cabang Tabanan - Dewi, Ni Putu Candra; Wimba, I Gusti Ayu; Mashyuni, IA. (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Job stress and job satisfaction are factors that are often referred to as the cause of turnover intention. Seeing this, this study was made to see the relationship between job stress and job satisfaction with turnover intention both partially and simultaneously. The research location at PT. Daya Anugrah Mandiri Tabanan Branch. 37 respondents were selected to be the research sample which later the data will be processed using multiple linear regression analysis techniques. From the test results, it was found that job stress has a significant positive relationship with turnover intention, a significant negative relationship occurs between satisfaction and turnover intention, and simultaneously work stress and satisfaction affect turnover intention. The magnitude of the influence of the independent variable on turnover intention is 72.9%. Suggestions in this study are PT Daya Anugrah Mandiri Tabanan Branch is expected to always provide working time in accordance with standard working hours, increase the salary given to employees.